Analisa Metode Pengukuran Berat Badan Manusia Dengan Pengolahan Citra - Hilman Fauzi; Fadlur Rahman; Tauhid Nur Azhar; Nasya Ayudina; Ratri Dwiatmaja (Diponegoro University, 2017)
Body weight is one of the most important parameters to determine the condition of a person's body. To find out information about the weight is generally done by using a measurement scales. However, there are several methods that can be done to determine a person's weight, one of which is by using image processing. Through this study, we tried to decipher the possibility of weight calculation using image processing with various mathematical approach based on a calculation of body surface area (BSA) and the volume of the ellipse for the human body. We process the image in the form of digital photos to generate information on the person's weight on the photo. Furthermore, we did investigate the possibility, calculation, and analysis of the accuracy of the system. To determine the performance of the system that we made, we did the comparison calculation results with body weight results of the scales. As a result, we conclude that the weight calculation method is feasible through image processing with various conditions and restrictions, it is confirmed by the results of the analysis and the accuracy of our calculation system is 95% at a distance of 470 cm between the camera and the object.